Collagen-Induced Platelet Aggregation: The Role of Adenine Nucleotides and the Release Reaction - Kattlove, Herman; Gomez, M. Hugo (Thrombosis and Haemostasis, 1975)
Collagen-induced platelet aggregation is associated with the release of ADP and the catabolism of radioactive ATP. These studies demonstrate that the amount of human platelet ADP released and ATP catabolized increase with time of stirring of the collagen-platelet rich plasma (PRP) mixture and with increasing amounts of collagen. These changes in adenine nucleotides occurred simultaneously with the aggregation. No early changes preceding aggregation were noted. Stirring the collagen-PRP mixture maximized ADP release and ATP catabolism; some ADP release and ATP catabolism occurred with minimal agitation. Incubation of PRP with metabolic poisons (2-deoxyglucose with either KCN or oligomycin), which lowered platelet ATP content, also reduced collagen-induced release of ADP and aggregation. However, platelet adhesion to collagen was unaffected by metabolic poisons. These data suggest that collagen directly stimulates ADP release. The demonstration of release in EDTA–PRP further suggests that platelet aggregation is not required for collagen-induced ADP release.